Platelet counts in epileptic children receiving valproic acid - Lilik Indrayati; Fadhilah Tia Nur; Bambang Soebagyo (Paediatrica Indonesiana, 2020)
Background Epileptic seizures are a transient occurrence resulting from abnormal, excessive, or synchronous neural activity in the brain. Epilepsy requires long-term treatment, increasingly larger doses, and combination therapy. Anti-epileptic drugs (AEDs), especially valproic acid (VPA), are the main treatment of choice. Thrombocytopenia is the most common adverse event from AEDs. Objective To evaluate platelet counts in epileptic children receiving valproic acid monotherapy vs. polytherapy. Methods This analytic, observational, retrospective cohort study was conducted in children with epilepsy below 18 years of age and treated in Dr. Moewardi Hospital, Surakarta, Central Java. Subjects had received VPA treatment for at least 6 months, either as monotherapy or polytherapy. There were 40 subjects in each group (VPA monotherapy vs. VPA polytherapy). The exclusion criteria were patients who had thrombocytopenia and did not take valproic acid regularly. The data was taken from laboratory and the outcome assessed was decreasing of platelet count. Results Administration of VPA as monotherapy vs. polytherapy was not significantly associated with incidence of thrombocytopenia. However, duration of VPA use > 2 years was associated with significantly greater proportion of thrombocytopenia, with OR 33.0 (95%CI 4.157 to 261.962; P=0.001) compared to VPA use < 2 years. Similarly, VPA dose of >30 mg/kg/day was significantly associated with greater proportion of thrombocytopenia, with OR 4.081 (95%CI 1.337 to 12.458; P=0.013) compared to <30 mg/kg/day dosage. Conclusion Incidence of thrombocytopenia is not significantly different between VPA as a monotherapy and polytherapy. However, higher VPA dose and longer VPA duration are associated with higher proportion of thrombocytopenia.